KRYMINALIZACJA OBRAZY UCZUĆ RELIGIJNYCH W POLSKIM PRAWIE KARNYM - Żukowska, Małgorzata (Zeszyty Prawnicze, 2016)
The Criminalisation of Insult to Religious Feelings in Polish Criminal Law Summary The article discusses the criminalisation of conduct that is offensive to another person’s religious feelings under the Polish Penal Code. The first part presents arguments against the recognition of such behaviour as an offence. The next part gives arguments showing that it must be treated as an offence. The author discusses offences against freedom of conscience and religion from the perspective of the principle of the secular state and its neutrality on worldview. The article also refers to grounds for the criminalisation of conduct which is offensive to another person’s religious feelings, the offence defined in Article 196 of the Polish Criminal Code, in the light of freedom of speech. The construction of Article 196 is analysed from the point of view of comparative law and compared to other European legal systems.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />